Evaluation of reactive Epstein-Barr virus (EBV) in Iranian patient with different subtypes of multiple sclerosis (MS) - Nourollah Ramroodi; Abbas Ali Niazi; Nima Sanadgol; Zohre Ganjali; Vida Sarabandi (Brazilian Journal of Infectious Diseases, 2013)
OBJECTIVES: Epstein-Barr virus has been recently associated with the onset of multiple sclerosis, yet understanding how it elicits autoimmunity remains elusive. We investigated the relation between Epstein-Barr virus reactivation and disease development in different subtypes of multiple sclerosis. METHODS: In the present research, we have determined the Epstein-Barr virus-DNA load by quantitative real-time polymerase chain reaction and Epstein-Barr virus antibody levels by EIA technique in both multiple sclerosis patients (n = 78) and healthy controls (n = 123). RESULTS: Our results demonstrated increased titer of both anti-Epstein-Barr virus-IgG and IgM antibodies in patients (91.02% vs 82.11% in controls, p < 0.001 and 14.1% vs 4.06% in controls, p < 0.001, respectively). Overall, Epstein-Barr virus reactivation was found in 68.75% of subtypes of multiple sclerosis, 4.54% of multiple sclerosis primary subtype, and in only 3.25% of healthy control subjects. Moreover, in samples of patients with disease relapse (exacerbation) cell free viral DNA was elevated in contrast to other patients (p < 0.001). CONCLUSIONS: These findings provide further support for the detrimental effects of Epstein- Barr virus in the reactivation of multiple sclerosis attacks.